The use of online resources to Fosrter Impromptu Speech in a group of eighth graders - Aguilar Meléndez, Mirtian (2023)
This dissertation is targeted to analyze the effect of the most pertinent online resources, such as making videos, on enhancing students' impromptu speech speaking skill. Equally important, the study aims for identifying the online sources which students use in the English classes, such as hardware and software. Besides, this research applies the impromptu speech practice to teach the speaking skill in English when students use online sources (video-based). Finally, the main aim analyzes the results of implementing impromptu speech practice to teach the speaking skill in English by using online resources (ICTs).